Portable polysomnography for sleep monitoring in elite youth rowing: An athlete's gain or the sleep's thief? - Hof zum Berge, A.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (Translational Sports Medicine, 2021)
Portable polysomnography (PSG) is a promising tool to assess sleep architecture and stages in athletes, yet there are hardly any research findings concerning comfort and practicability within the applied field. Thus, aim of this study was to examine to what extent self-applied portable PSG has an influence on objective (measured via actigraphy) and subjective (measured via sleep log) sleep parameters. Consequently, it should be assessed in how far the use of a portable PSG in sport-scientific field investigations is reasonable. The study sample included thirteen elite youth rowers (Mage = 16.31 ± 0.63 years; Mheight = 187.23 ± 5.3 cm; Mweight = 81.92 ± 7.59 kg) of the German Rowing Federation. During a preparational training camp with standardized sleeping conditions, athletes engaged in a supervised sleep monitoring. Participants kept a sleep log (for subjective evaluation of sleep) and wore an actigraphy bracelet (for objective evaluation of sleep) on four consecutive days. Further, athletes applied a portable PSG device on two consecutive nights in randomized order. Results indicate no significant differences between nights with and without the application of portable PSG for all objective and subjective sleep parameters. Its use seems to be reasonable without affecting sleep quality significantly. Hence, portable PSG may be installed whenever the assessment of sleep architecture seems desirable and information cannot be adequately attained by actigraphy.